Urgensi Nilai-Nilai Cinta Tanah Air Dalam Upaya Penangkalan Radikalisme Pada Generasi Remaja - Rizqi Abdillah; Fachrudin, Akhmad; Nasekha, Ati Dina; Laila, Nur; Umami, Ana Rahma; Nadia, Siti Rofiatun; Suryani, Asyifa; Risiq, Sidny; Astuti, Puji; Fauzan, Sahrul; Ziyaurrohman, Ahmad (Profetik: Jurnal Pengabdian Masyarakat, 2023)
Seeing the environmental conditions of the Pedeslohor village which is diverse with cultures and religions, it is necessary to prevent radicalism, especially among teenagers. The people of Pedeslohor village are still lagging behind in terms of culture and religion. Like the influence of community organizations in Pedeslohor village which is still very minimal, the community can still be mapped based on cultural and religious elements. Against this background, it is necessary to emphasize the deterrence of radicalism in order to maintain the existence of man and Islam in the Pedeslohor village community. Countering this radicalism was carried out with the formation of the Nahdlatul Ulama Student Association (IPNU) and the Nahdlatul Ulama Girls Student Association (IPPNU) movements under the autonomous body of the Nahdlatul Ulama (NU) community organization. The existence of the IPNU and IPPNU movements was also carried out with education for love of the motherland.